Assessing the problem of gender inequality in deliberative democracy. - Dillard, Kara Noelle (Kansas State University, 2011)
In deliberative democracy, attempts to reconcile questions of gender and civil society are deadlocked over fundamental assumptions concerning the role of deliberation and the possibility that exclusion and inequality are inherent in democracy. Normative theories of deliberation - encouraging free, equal and impartial participation by citizens are fueled by the power of reason. Reason giving is associated with dominant groups – namely white, middle-class men; passionate, emotive and particularized speech is associated with politically disadvantaged groups such as women, minorities and poor. Limited empirical findings indicate rational models of deliberation do not affirm theorized inequalities. In this case, female participants neither experience unequal access or treatment within deliberation. This dissertation seeks to provide a framework for resolving the debate posed by difference democrats over whether deliberative democracy remedies the problem of inequality by examining fourteen National Issues Forums public deliberations. One set of deliberations feature an equal mix of male and female participants, another set with more male than female and a third with more female than male participants. I examine the types of talk women and men use in deliberations and whether affective claims negatively affect deliberation. Ultimately, I find that inequality based on gender exists in most of the deliberative forums I surveyed. I argue that the type of inequality plaguing deliberative democracy exists a priori – before participants enter the forums – and then manifests itself inside the forum as well. The normative structure of deliberation that is supposed to screen or bracket out inequality and the strong influences of the economic and political elites just does not happen to the degree deliberative democracy needs in order to continue the claim that it is net beneficial over the status quo.
Keywords: Deliberative democracy; National Issues Forums; Gender; Deliberation; Civic engagement; Sociology (0626)